2000
DOI: 10.1007/s005950070089
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial metastasis from renal cell carcinoma: Report of a case

Abstract: A case of endobronchial metastasis from renal cell carcinoma developing 5 years after a right nephrectomy in a 63-year-old man is reported. Bronchoscopic examination performed after the patient presented with hemoptysis showed a polypoid tumor obstructing the entrance to the left upper bronchus. A snare was introduced through a bronchofiberscope to remove the endobronchial tumor, following which his atelectasis improved remarkably and his hemoptysis resolved. No side effects were observed. Electrosurgical snar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Other conventional procedures, chemotherapy and local radiotherapy, were excluded from the patients' intraluminal-therapeutic strategy because these treatments were not thought to be effective against metastatic lesions of renal cell carcinoma. Sakumoto et al reported the usefulness and safety of diathermic snares in palliative treatments for EBM of renal cell carcinoma (16). Although diathermic snares are useful in cases of polypoid lesion with a small base attachment, the instruments are not always useful for flat lesions or for those with large base attachments (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other conventional procedures, chemotherapy and local radiotherapy, were excluded from the patients' intraluminal-therapeutic strategy because these treatments were not thought to be effective against metastatic lesions of renal cell carcinoma. Sakumoto et al reported the usefulness and safety of diathermic snares in palliative treatments for EBM of renal cell carcinoma (16). Although diathermic snares are useful in cases of polypoid lesion with a small base attachment, the instruments are not always useful for flat lesions or for those with large base attachments (17).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, other techniques, including electrocoagulation or the use of lasers, may be more effective and convenient (3). Sakumoto et al discussed bleeding as the most serious complication in their report (16), and sometimes a blood transfusion was needed for patients suffering gastrointestinal metastasis of renal cell carcinoma (18). Thus, in the endoscopic treatments of airway obstructions due to metastatic renal cell carcinoma, preparations for massive bleeding are essential.…”
Section: Discussionmentioning
confidence: 99%
“…Most common symptoms are cough, hemoptysis, dyspnea and wheezing in the context of recurrent pulmonary infections due to local atelectasis [1][2][3][4][5]7]. In rare cases, patients with EBM may be totally asymptomatic [10].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] This case, while demonstrating some of the potential appearances of intrathoracic metastases from renal cell carcinoma that an interventional bronchoscopist may encounter, also serves to extend this warning to EBUS-TBNA of nodal metastases. There are several case reports that warn against the risk of bronchoscopy in the presence of endobronchial metastases from renal cell carcinoma, in particular the risk of hemorrhage.…”
Section: Discussionmentioning
confidence: 99%